ENTREPRENEURSHIP EDUCATION PROCESS IN FORMING STUDENTS PRENEUR AT SUNAN PONDOK PESANTREN VOCATIONAL SCHOOL DRAJAT LAMONGAN - Rini, Diah Ayu Sulistio; Winarno, Agung (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2023)
The entrepreneurial education process in forming students is entrepreneurial education Which teach Students period now Which sued For No only deepen religious knowledge, but also able to be independent and entrepreneurship. This aim is to find out that: (1) can find out the entrepreneurship education curriculum in forming santripreneurs at the Sunan Drajat Lamongan Islamic boarding school vocational school (2) can find out the process of entrepreneurship education in forming students at Pondok Vocational School Boarding school Sunan Degree Lamongan (3) can know factor supporter And Barriers to the implementation of entrepreneurship education in forming students at the Sunan Drjat Lamongan Islamic boarding school vocational school . Results from study This is known that: (1) For application learning entrepreneurship in high school sunan degree Lamongan Already walk with Good in accordance with curriculum 2013 Which consisting of 30% theory 70% applicable field practice with learning still the same offline (2) SMK sunan degree Lamongan own effort separately For process grow soul Student entrepreneurship, one of which is through training conducted by teachers and students at Sunan Vocational School degree Lamongan with trainings education entrepreneurship This student will in teach good entrepreneurship methods as well as guide teachers so that learning is as creative as possible in order to motivate students (3) teachers and students realize that there are several things that can be inhibiting factors in the entrepreneurial learning process that are experienced or felt by students and teachers. However, this does not dampen their enthusiasm for learning entrepreneurship. Even though at first it is forced and only for good grades, everyone will get used to it and they will like it. Apart from that, the presence of supporting factors can make them more optimistic and have greater enthusiasm in learning entrepreneurship Because they consider bring learning entrepreneurship This will repair their lives because they have entrepreneurial knowledge that they can use to open their own jobs. The suggestions given by researchers are expected to be able to develop research about implementation learning entrepreneurship This in school other or in the environment society and dig deeper to find out to what extent we have entrepreneurial knowledge and are able to apply it in our lives so that we can improve our lives with the knowledge we have, namely the soul. businessman